DO THE WORK! : CLEAN WATER AND SANITATION - Knutson, Julie (Ann Arbor, Michigan : Cherry Lake Publishing, 2022)
"Readers will learn about the sixth UN Sustainable Development Goal and what it takes to commit to the availability of clean water and sanitation for all by 2030. Aligned to curriculum standards, this book also highlights key 21st Century content: Global Awareness, Public Policy, Health and Wellness, Civics Literacy, and Environmental Stewardship. Includes a table of contents, glossary of key words, index, author biography, sidebars, and infographics"-- Provided by publisher
Includes index
Bibliography: page 30
Grades 4-6
Keywords: Sustainable development -- Juvenile literature; Water -- Purification -- Juvenile literature; Water quality -- Juvenile literature